Analisis Pengaruh Pendapatan dan Jumlah Anggota Rumah Tangga Petani Kelapa Sawit Terhadap Pola Konsumsi Pangan Berbasis PPH di Desa Bagan Sapta Permai Kabupaten Rokan Hilir, Riau - Sinambela, Sarah Patresia Arauli; Gayatri, Siwi; Mukson, Mukson (Universitas Galuh, 2025)
The income of oil palm farmers is inseparable from the selling price of palm oil, where the price fluctuates so that it will have an impact on farmers' income and will affect the food consumption of farmers and their families. Food consumption can be measured through the achievement of values, composition, food patterns and nutrition that are balanced with the Desirable Dietary Pattern (PPH) indicator in order to achieve food standards. This study aims to calculate the income of oil palm farmers, calculate the farmers' expected food pattern (PPH) score, and analyze the influence of income and the number of household members on the food consumption pattern based on PPH of oil palm farmers. This research was carried out in May – June 2024 in Bagan Sapta Permai Village, Rokan Hilir Regency, Riau using a survey method. The data collection method used was an interview with a 2 x 24-hour food recall questionnaire tool and sampling was carried out using a purposive sampling technique of 53 farmers. The data analysis method used for this study is the multiple linear regression method to determine the influence of oil palm farmer income (X1) and the number of household members (X2) on food consumption patterns based on PPH (Y). The results of the study showed that the average income of farmers was Rp 7,512,339.62 per month with the average score of PPH-based food consumption patterns was 88,53. The income variable (X1) and the number of household members (X2) simultaneously affect the PPH-based food consumption pattern (Y). The income variable partially had an inverse effect on the PPH-based food consumption pattern and the variable the number of household members had an direct influence on the PPH-based food consumption pattern.